Throughput And Tester Utilization Improvement In The Hard Disk Drive Assembly Line Using Hybrid Simulation Approach - Asih, Hayati Mukti; Chong, Kuan Eng (American Scientific Publishers, 2014)
Manufacturers of high mix and high volume products are forced to focus on strategic capacity planning in their production system to remain competitive. This work is based on a case study in a hard disk drive manufacturing company with the objective of improving the throughput and tester utilization in the testing assembly line. The problem is complex as there were multiple products, each product model undergoing different testing routes and testing duration. This is further complicated by 2 different fixed capacity testers where each tester is mix-loaded with different products. As the scenario is too complex to be solved by analytical methods, a hybrid simulation approach was proposed to find a feasible solution to the problem. The problem was first formulated with a mathematical model to optimize the number of testers with predefined configurations. Each configuration was then simulated to determine the throughput and tester utilization. Finally the TOPSIS and AHP methods were employed to determine the best configuration. The results of the proposed method improved throughput and tester utilization by 6.71% and 26.67%, respectively.